Milton santos and the 21th century: scientific technical informational environment for the comprehension of present-future (PerCursos, 2022)
To comprehend the mutations recently engendered by the techniques in the world of work, in the forms of production of violence and the access to public labor and social security policies are the main challenges of this article, which seeks to comprehend the role of space and geographic science today. Based on this statement, Milton Santos' work is strategic for understanding the Present. In this way, the article focuses on the category of technical-scientific informational means created by the author as a theoretical and methodological possibility for the analysis of the updating of forms of hegemony that feed on technique as essential in the exercise of domination. The study is also dedicated to understanding the adoption of information and data technologies in the service of contributors to the social security system.
Keywords: Milton Santos; geographic space; technique; social security policy